Nanoscale mapping of heterogeneity of the polarization reversal in lead-free relaxor–ferroelectric ceramic composites. Issue 4 (5th January 2016) - Gobeljic, D.; Shvartsman, V. V.; Belianinov, A.; Okatan, B.; Jesse, S.; Kalinin, S. V.; Groh, C.; Rödel, J.; Lupascu, D. C.
Abstract : Heterogeneity of domain patterns and polarization switching in ferroelectric–relaxor ceramic composites were addressed using piezoresponse force microscopy. Abstract : Relaxor/ferroelectric ceramic/ceramic composites have shown to be promising in generating large electromechanical strain at moderate electric fields. Nonetheless, the mechanisms of polarization and strain coupling between grains of different nature in the composites remain unclear. To rationalize the coupling mechanisms we performed advanced piezoresponse force microscopy (PFM) studies of 0.92BNT–0.06BT–0.02KNN/0.93BNT–0.07BT (ergodic/non-ergodic relaxor) composites. PFM is able to distinguish grains of different phases by characteristic domain patterns. Polarization switching has been probed locally, on a sub-grain scale. k -Means clustering analysis applied to arrays of local hysteresis loops reveals variations of polarization switching characteristics between the ergodic and non-ergodic relaxor grains. We report a different set of switching parameters for grains in the composites as opposed to the pure phase samples. Our results confirm ceramic/ceramic composites to be a viable approach to tailor the piezoelectric properties and optimize the macroscopic electromechanical characteristics.